Peningkatan Hasil Belajar Biologi Siswa dengan Model STAD Pada Konsep Jaringan Tumbuhan: (Improving Students' Biology Learning Outcomes with the STAD Model on the Concept of Plant Tissue) - Rahmi Fitri Yusri; Siti Nurhalijah Siti Nurhalijah; Pricillia Humaira Pricillia Humaira; Putri Fatmaya Putri Fatmaya; Suci Novany Suci Novany; Annisa Purba Annisa Purba (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2023)
In a teaching and learning process, apart from the teacher, there are two very important elements, namely teaching methods and learning media. Learning has several models or learning approaches, one of which is cooperative learning. Cooperative learning is a learning approach that focuses on using small groups of students to work together and maximize learning conditions to achieve learning objectives. Student teams achievement division (STAD) learning is a type of cooperative learning that emphasizes interaction between students to motivate each other and help each other in mastering the material and achieving maximum achievement. This study aims to determine the improvement of students' biology learning outcomes with the stad type cooperative learning model on the concept of plant tissue. This research method is literature review. Literature review is a literature search and research by reading various books, journals, and other publications related to the research topic, to produce an article related to a particular topic. Based on the above discussion, it is concluded that the use of the STAD type cooperative learning model has a significant effect on improving student biology learning outcomes on the concept of plant tissue. Key words: Education, Learning, Cooperative, and STAD ABSTRAK Proses belajar mengajar, selain guru ada dua unsur yang amat penting yaitu metode mengajar dan media pembelajaran. Pembelajaran memiliki beberapa model atau pendekatan pembelajaran, salah satunya adalah pembelajaran kooperatif. Pembelajaran kooperatif merupakan suatu pendekatan pembelajaran yang berfokus pada penggunaan kelompok kecil siswa untuk bekerja sama dan memaksimalkan kondisi belajar untuk mencapai tujuan belajar. Pembelajaran student teams achievement division (STAD) merupakan salah satu tipe pembelajaran kooperatif yang menekankan interaksi diantara siswa untuk saling memotivasi dan saling membantu dalam menguasai materi dan mencapai prestasi secara maksimal. Penelitian kali ini bertujuan untuk mengetahui peningkatan hasil belajar biologi siswa dengan model pembelajaran kooperatif tipe stad pada konsep jaringan tumbuhan. Metode penelitian ini adalah literature review. Literature review adalah suatu penelusuran dan penelitian kepustakaan dengan membaca berbagai buku, jurnal, dan terbitan-terbitan lain yang berikaitan dengan topik penelitian, untuk menghasilkan suatu tulisan yang berkenaan dengan suatu topik tertentu. Berdasarkan pembahasan diatas, disimpulkan bahwa penggunaan model pembelajaran kooperatif tipe STAD berpengaruh signifikan terhadap peningkatan hasil belajar biologi siswa pada konsep jaringan tumbuhan. Kata kunci: Pendidikan, Pembelajaran, Koopertaif, STAD